Estructura horizontal de especies comerciales del bosque de colina baja de la concesión forestal 16-LOR/CON-MAD-2021-2014, distritos de Mazán y Napo, Loreto, 2022 - Mozombite Zambrano, Paolo (2023)
The horizontal structure of commercial species of the low hill forest of forest concession 16-LOR/CON-MAD-2021-2014, districts of Mazán and Napo, Loreto, was determined. Data from the forest census of commercial species was evaluated. In total, 1820 trees grouped into 23 forest species and eight botanical families were recorded. The distribution of the number of trees by diameter class is 0,87 trees/ha (1820 trees), where Anaueria brasiliensis (0,19 trees/ha, 398 trees), Albizia subdimidiata (0,11 trees/ha, 234 trees), Osteophloeum platyspermum (0,09 trees/ha, 207 trees) and Cedrelinga cateniformis (0,09 trees, 205 trees), show the highest number of trees. The diameter class of 60 cm to 70 cm contains the largest number of trees (0,27 trees/ha, 565 trees), followed by 50 cm to 60 cm (0,26 trees, 541 trees) and 70 cm to 80 cm (0,12 trees/ha, 261 trees). Ecologically, Anaueria brasiliensis (Lauraceae) is the most important with an IVI of 45,48, followed by Cedrelinga cateniformis “tornillo” (40,.87%), Albizia subdimidiata “pashaco” (31,63%), Osteophloeum platyspermum “cumala llorona” (26,06%) and Tachigali tessmannii “tangarana de altura” (23,91%). The results indicate a highly significant difference between the averages of the horizontal structure between species.